"A slippery slope": a scoping review of the self-injection of unlicensed oils and fillers as body enhancement. Issue 4 (February 2021) - Brennan, Rebekah; Overbye, Marie; Van Hout, Marie Claire; McVeigh, James
Highlights: Self-injection of body fillers, despite being a longstanding practice, has been largely linked to distinct cultural groups in recent times, for example, for example, bodybuilding communities. It was found that the majority of people who inject body fillers are male and do so to grossly increase muscle size, despite the stigmatisation this attracts within male body enhancement culture. Injection of oils and other materials in the male genitalia was also described, in addition to female self-injection in the breast, hand and leg areas for augmentation. A range of health consequences including paraffinoma, ulcers, migration of filler, deformation, pneumonia and one fatality are reviewed. Although relatively rare, the injection of body fillers warrants future research attention, including qualitative interviews with people who inject, considering the documented increase in DIY facial fillers and contemporary body image culture, supported by unrealistic social media discourse. Abstract: Self-injection of a range of oils and fillers for body enhancement dates back to 1899, but due to significant associated harms and fatalities this practice has been largely linked to distinct cultural groups in recent times. This scoping review gathers what is currently known on the self injection of body fillers for aesthetic purposes, using Arksey and O'Malley's (2005) five stage iterative process scoping review methodology. Thematic manual coding then organised the data into themes through identified patterns: indicative profiling of individuals who self inject body fillers; motivation for use across types of oil injection; sourcing routes and documented harms. It was found that the majority of people who inject body fillers are male and do so to grossly increase muscle size. Injection of oils and other materials in the male genitalia was also described, in addition to female self-injection in the breast, hand and leg areas for augmentation. A range of health consequences were reviewed. Recommendations are made for further research into this unique phenomenon, which although is relatively rare warrant future research attention considering the documented increase in DIY facial fillers and contemporary body image culture.